Normal Phonation Duration - G, Purushothanma; KN, Shashidhar; GN, Rangamani (Journal of All India Institute of Speech and Hearing)
Phonation is a complex activity. Voice is very versatile. Phonation duration varies among individuals. Phonation duration depends on the amount of air available on exhalation and many other factors. Some of the variables that effect phonation duration are.